Genetic And Biotechnological Advances in Plant-Based Geroprotectors: Toward Molecular Strategies for Healthy Aging - Shukrullozoda R. Sh.; Shukrullozoda N. Sh. (Scientific Trends, 2025)
Plant-based geroprotectors represent a promising class of natural compounds capable of slowing down aging and promoting increased lifespan. This review explores recent advancements in biotechnology and genetic engineering, including genome editing (CRISPR/Cas9), omics approaches, and in vitro culture methods, all aimed at enhancing the bioavailability and efficacy of phytochemicals with geroprotective properties. The molecular mechanisms of action of key compounds (resveratrol, polydatin, flavonoids) are summarized, along with data from preclinical and clinical studies. In addition, the review highlights current challenges and future perspectives regarding the integration of these substances into clinical practice.
Keywords: Geroprotectors, phytochemistry, CRISPR/Cas9, resveratrol, aging, biotechnology, signaling pathways SIRT1, AMPK, mTOR.